Architectural innovation in China: The concept and its implications for institutional analysis - Marcus Conlé (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2015)
Chinas rapid economic ascent has been accompanied by brilliant institutionalist scholarship elaborating on the significance of institutional diversity for Chinas recent development trajectory. As valuable as these analyses are, their foundation in the transition literature seems to have resulted in their focusing mainly on offering explanations for the characteristics and the (temporary) persistence of institutional diversity rather than on providing insights about the impact of that diversity on such issues as innovation and competitive advantage. This focus has arguably contributed to both, a limited understanding of Chinas development model as well as a limited impact of the findings concerning Chinas institutional reality on the research program of the comparative capitalisms, specifically on the debate on the benefits and flaws of the so-called Varieties of Capitalism (VoC). Building on recent work on innovation in China, the present paper seeks to provide a typology of architectural innovation, a concept that was originally introduced by Rebecca Henderson and Kim Clark as an extension to the radical/incremental innovation typology, in order to capture the main features of a pattern that appears to be found in a great number of Chinas (assembly) industries. After illustrating this pattern with the help of an exemplary case study of Chinas passenger vehicle sector, the paper will give a brief discussion of how institutional diversity and the various roles of government relate to the identified pattern of innovation.
Keywords: 330; China; varieties of capitalism; architectural innovation; assembly industries; passenger vehicles